Iron corrosion by novel anaerobic microorganisms - Dinh, Hang T.; Kuever, Jan; Mußmann, Marc; Hassel, Achim W.; Stratmann, Martin; Widdel, Friedrich (Nature (London), 2004)
Corrosion of iron presents a serious economic problem. Whereas aerobic corrosion is a chemical process 1 , anaerobic corrosion is frequently linked to the activity of sulphate-reducing bacteria (SRB) 2 , 3 , 4 , 5 , 6 . SRB are supposed to act upon iron primarily by produced hydrogen sulphide as a corrosive agent 3 , 5 , 7 and by consumption of ‘cathodic hydrogen’ formed on iron in contact with water 2 , 3 , 4 , 5 , 6 , 8 . Among SRB, Desulfovibrio species—with their capacity to consume hydrogen effectively—are conventionally regarded as the main culprits of anaerobic corrosion 2 , 3 , 4 , 5 , 6 , 8 , 9 , 10 ; however, the underlying mechanisms are complex and insufficiently understood. Here we describe novel marine, corrosive types of SRB obtained via an isolation approach with metallic iron as the only electron donor. In particular, a Desulfobacterium -like isolate reduced sulphate with metallic iron much faster than conventional hydrogen-scavenging Desulfovibrio species, suggesting that the novel surface-attached cell type obtained electrons from metallic iron in a more direct manner than via free hydrogen. Similarly, a newly isolated Methanobacterium -like archaeon produced methane with iron faster than do known hydrogen-using methanogens, again suggesting a more direct access to electrons from iron than via hydrogen consumption.